\(\dfrac{x^2-1}{x-1}=4\left(x\ne1\right)\)
\(\Leftrightarrow\dfrac{x^2-1}{x-1}-4=0\)
\(\Leftrightarrow x^2-1-4\left(x-1\right)=0\)
\(\Leftrightarrow x^2-1-4x+4=0\)
\(\Leftrightarrow x^2-4x+3=0\)
\(\Leftrightarrow\left(x-3\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\left(n\right)\\x=1\left(l\right)\end{matrix}\right.\)
\(S=\left\{3\right\}\)
|x2 - 1| : (x -1) = 4
<=> |x2 - 1| = 4. (x -1)
<=> |x2 - 1| = 4x -4
TH1: x2 - 1 \(\ge\) 0 <=> x2 \(\ge1\)
x2 - 1 = 4x -4
<=> x2 - 4x + 3 = 0
<=> x = 3 hoặc x = 1 (tm)
TH1: x2 - 1 \(\le\) 0 <=> x2 \(\le1\)
1 - x2 = 4x -4
<=> - x2 - 4x + 5 = 0
<=> x = 1 hoặc x = -5 (tm)